Treatment of nasolacrimal duct obstruction with probing in children younger than 4 years - Mrugacz, Małgorzata; Sielicka, Danuta; Bakunowicz-Łazarczyk, Alina (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: To evaluate the efficacy of nasolacrimal duct probing as the treatment of nasolacrimal duct obstruction in children younger than 4 years. Material and methods: A total amount of 320 eyes in 275 children 4 to 48 months old, receiving nasolacrimal duct probing were enrolled in a retrospective study. The patients were divided into 4 groups depends on age: I group – 4-12 months, II group – 12- -24 months, III group – 24-36 months and IV group – 36-48 months. Results: The percentage of efficient duct probing was: in I group – 84%, in II group – 79%, in III group – 78% and in IV group – 59%. Conclusions: In children 4 to 36 months old, probing is a successful treatment of nasolacrimal duct obstruction with no decline in treatment success with increasing age.